Evaluation of Antibacterial Potential of Biosynthesized Plant Leave Extract Mediated Titanium Oxide Nanoparticles using Hypheae Thiebeace and Anannos Seneglensis - H. Hassan; K.I. Omoniyi; F.G. Okibe; A.A. Nuhu; E.G. Echioba (Journal of Applied Sciences and Environmental Management, 2019)
The need for new antimicrobial agent has drawn attention on developing new and emerging materials based on nanoparticles with antimicrobial activity. The aim of this research was to evaluate the antibacterial activity of nanoparticles of titanium dioxide. A green synthesis of TiO2 nanoparticles was done using a plant extract of H. thelbiecea and Ananos seneglensisa The presence of various photochemical like flavonoids, steroids, polyphenols, and terpenoids was investigated by following standard biochemical methods. The titanium oxide nanoparticles (TiO2 NPs) synthesized was confirmed by their change of colour to brown and reddish brown due to the phenomenon of surface Plasmon resonance. The characterization studied was done by UV-vis spectroscopy, scanning electron microscopy (SEM), X-Ray diffraction (XRD) and Fourier Transmission infrared spectroscopy (FTIR). The green synthesized TiO2 NPs excitation was confirmed using UV–Vis spectrophotometer at 270 and 290 nm. SEM revealed that the synthesized TiO2 NPs are spherical and crystalline in nature. The overall sizes are 40 and 50 nm for H. thelbiecea and Ananos respectively. FTIR spectroscopy analysis showed the presence of flavonoid, polyphenols and amide groups likely to be responsible for the green synthesis of titanium oxide nanoparticles using H. thelbiecea and Ananos seneglensis aqueous leaf extracts .The XRD pattern showed the characteristic Bragg peaks of (111), (200), (220) and (311) facets of the anatase titanium oxide nanoparticles and confirmed that these nanoparticles are crystalline and spherical in nature. The two plants used to synthesized titanium oxide nanoparticle (H. thelbiecea and ananos seneglensisa) showed good antimicrobial activity against clinically important pathogens.. The antimicrobial study of TiO2 NPs shows that 20 μg/ml TiO2 NPs is effective for complete inactivation of Gram positive, Gram negative as well as fungal cultures. This effective microbial inactivation is mainly attributed to its ability to cause damage to the cell membrane.